Factors Affecting the Service Quality of Office of Provincial Public Prosecution of Chanthaburi - Montha, Waranya; Phochathan, Suthasinee (Ratchaphruek Journal, 2022)
This research objectives were to study 1) level of the factors influencing service quality, 2) opinions on the service quality, and 3) factors influencing service quality of the Office of Provincial Public Prosecution of Chanthaburi. The sample group was 400 police officers and service recipients at the Office of Provincial Public Prosecution of Chanthaburi. Calculated using the formula of W.G. Cochran (1953), 95% confidence level, and the ratio of service recipients was determined to be 30%: 70, including 120 police officers and 280 service users by using random sampling methods The research instrument was a questionnaire which was divided into 3 parts as follows: Part 1, a question about personal factors, Part 2, a questionnaire with 20 items on the level of factors determining the quality of service. The confidence value was 0.953. Part 3, a questionnaire with 20 items about the level of service quality, with the confidence value of 0.933 and the confidence value of the whole letter was 0.967. The research Statistics was descriptive statistics consisted of percentage, frequency, mean, standard deviation, and Simple Multiple Regression. The result showed 1) factor influencing service quality was at highest opinion in each aspect in service staff, 2) service quality was at the high level. When considering each aspect, it was found that the highest opinion was the aspect in confidence and trust in service, 3) factors influencing service quality was at significance level of .05 in descending order were service staff, infrastructure, and place. The variables in 4 aspects could collectively predict the service quality at 59.70 percent.